Molecular Characterization of Streptococcus spp. Isolated from Milk, Feces and Farm Environment of Mastitic Dairy Cows (Journal of Science and Technology Research, 2024)
Streptococci are the primary cause of mastitis, significantly impacting the dairy industry economically. This study aimed to explore the molecular epidemiology, antimicrobial resistance, and virulence characteristics of Streptococcus spp. isolated from the milk, feces, and environment of dairy cows with mastitis. Sixty (60) samples (milk = 20, feces = 20 and soil = 20) from cows with clinical mastitis (CM) were purposively collected and examined. Samples were enriched in Luria Bertani broth (LB) and Streptococcus spp. was isolated on Modified Edwards Medium and confirmed by ribosomal (16S rRNA) gene sequencing. Twenty-two (36.67%) of the samples were positive for Streptococcus spp. (milk = 40.90%, feces = 31.82% and soil = 27.28%) by cultural and molecular examination. Phylogenetic analysis revealed 59.5, 30.5, 6.0% and 4.0 % of the Streptococcus isolates as S. uberis, S. agalactiae, S. hyovaginalis and S. urinalis, respectively. The milk samples had higher prevalence (42.75%) of S. uberis mastitis than feces (36.80%) and soil (20.45%) samples. Likewise, S. agalactiae was prevalent in 51.5%, 37.60% and 10.90% milk, feces and soil samples, respectively. The draft assembly sizes of G2M6 and G6M1 were 1,960,858 and 2,303,841 base pair (bp), respectively. The strains were typed as S. uberis sequence type 155 (ST155) and S. agalactiae sequence type 58 (ST58). The G2M6 genome contained 367 SEED subsystem features, 45 antimicrobial resistance genes (ARGs), and 160 virulence and virulence-related genes, whereas the G6M1 genome possessed 378 SEED subsystem features, 41 ARGs and 178 virulence genes. One plasmid replicon such as IncY of 4,012 bp, was identified in the G6M1 genome (with 95% identity and 60% coverage) while G2M6 genome harbored none. Genome completeness analysis using BUSCO revealed the presence of 100% complete BUSCOs in the hybrid assembly of both genomes. Streptococcus spp. associated with bovine mastitis exhibit a variety of genomic traits and harbor an array of ARGs and virulence genes. Further investigation is needed to identify specific traits that govern virulence fitness in the pathophysiology of mastitis.J. of Sci. and Tech. Res. 6(1): 01-12, 2024